Unusually slow intramolecular proton transfer dynamics of 4′-N, N-dimethylamino-3-hydroxyflavone in high n-alcohols: involvement of solvent relaxation. Issue 2 (26th January 2016) - Ghosh, Deborin; Batuta, Shaikh; Begum, Naznin Ara; Mandal, Debabrata
Abstract : The S1 energy surface of DMA3HF as a function of solvation and ESIPT coordinates, viewed down the energy axis as a 2-dimensional projection. Abstract : Excited state intramolecular proton transfer (ESIPT) time-constants of 4′- N, N -dimethylamino-3-hydroxyflavone (DMA3HF) in high n -alcohols – 1-butanol, 1-hexanol and 1-decanol – were measured to be 90 ps, 130 ps and 190 ps, respectively, which are unusually slow. At the same time, the solvation time-constants of the DMA3HF enol in the same set of solvents were measured as 100 ps, 150 ps and >300 ps, respectively. Thus, both the ESIPT and enol solvation time-constants in high n -alcohols increase monotonically with the alkyl chain-length of the solvent, although the increase is not strictly proportional. It appears that the H-bonding capacity of the solvent is the single major factor influencing both processes, causing them to become closely correlated. Solvation causes a drastic change in the solvent molecular configuration around the excited enol, E*, inducing the breakage of DMA3HF⋯solvent inter-molecular H-bonding, which in turn promotes ESIPT. Following previously reported theoretical work on ESIPT, a qualitative description of the S1 potential energy surface can be formulated, where the involvement of solvent relaxation with the ESIPT process is explained.